An observational, prospective study on surgical treatment of secondary mitral regurgitation: The SMR study. Rationale, purposes, and protocol. Issue 10 (13th August 2020) - Calafiore, Antonio Maria; Di Mauro, Michele; Bonatti, Johannes; Centofanti, Paolo; Di Eusanio, Marco; Faggian, Giuseppe; Fattouch, Khalil; Gaudino, Mario; Kofidis, Thoedoros; Lorusso, Roberto; Menicanti, Lorenzo; Prapas, Sotirios; et al.
Abstract: The natural history of secondary mitral regurgitation (MR) is unfavorable. Nevertheless, there are no evidence that its correction can improve the outcome. If from one side the original cause of secondary MR can be such to limit the possibilities of improvement, from the other side it is possible that the surgical technique widely applied to repair, restrictive mitral annuloplasty, is not adequate to correct the regurgitation. The addition of valvular and/or subvalvular techniques has been considered a possible technical solution. However, we do not know the prevalence of each technique, how many times mitral replacement is used to correct secondary MR. This aspect is of particular importance, as we know that a successful mitral repair causes a better left ventricular systolic remodeling than a unsuccessful repair or replacement. This study is a prospective, observational registry, conceived to understand what is done in the real world. Any surgeon will use the technique he thinks the most suitable for the patient. Every year, for 5 years, patients will have a clinical and echocardiographic follow‐up, to evaluate the risk factors for a worse result (death, rehospitalization for heart failure, reoperation for MR return, moderate, or more MR return). This knowledge will give us the possibility to understand which is the technique, or the strategy, more efficient to treat this disease and the real efficacy of the surgical treatment.